Lyl1-deficiency promotes inflammatory responses and increases mycobacterial burden in response to Mycobacterium tuberculosis infection in mice - Jones, Shelby-Sara; Ozturk, Mumin; Kieswetter, Nathan Scott; Poswayo, Sibongiseni K. L.; Hazra, Rudranil; Tamgue, Ousman; Parihar, Suraj P.; Suzuki, Harukazu; Brombacher, Frank; Guler, Reto (Frontiers in Immunology, 2022)
Lymphoblastic leukemia 1 (Lyl1) is a well-studied transcription factor known to exhibit oncogenic potential in various forms of leukemia with pivotal roles in hematopoietic stem cell biology. While its role in early hematopoiesis is well established, its function in mature innate cells is less explored. Here, we identified Lyl1 as a drastically perturbed gene in the Mycobacterium tuberculosis (Mtb) infected mouse macrophage transcriptome. We report that Lyl1 downregulation upon immune stimulation is a host-driven process regulated by NFκB and MAP kinase pathways. Interestingly, Lyl1-deficient macrophages have decreased bacterial killing potential with reduced nitric oxide (NO) levels while expressing increased levels of pro-inflammatory interleukin-1 and CXCL1. Lyl1-deficient mice show reduced survival to Mtb HN878 infection with increased bacterial burden and exacerbated inflammatory responses in chronic stages. We observed that increased susceptibility to infection was accompanied by increased neutrophil recruitment and IL-1, CXCL1, and CXCL5 levels in the lung homogenates. Collectively, these results suggest that Lyl1 controls Mtb growth, reduces neutrophilic inflammation and reveals an underappreciated role for Lyl1 in innate immune responses.